2005
DOI: 10.1016/j.mcna.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Envenomations

Abstract: Numerous types of envenomations may be encountered by health care workers depending on where in North America they work. Clinicians should be familiar with the animals in their region that may lead to envenomation.A rational approach with use of poison center or medical toxicology consultation services ensures that cases are managed appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 140 publications
0
10
0
1
Order By: Relevance
“…Most of the horses were treated with corticosteroids (13/15) and antimicrobials (13/15). The mouths of rattlesnakes have been shown to harbor a mixed population of bacteria, and although commonly accepted as standard of care in equine medicine, the use of antimicrobials in human snakebite victims is not deemed necessary . Corticosteroids have been used in the treatment of rattlesnake envenomation for decades .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the horses were treated with corticosteroids (13/15) and antimicrobials (13/15). The mouths of rattlesnakes have been shown to harbor a mixed population of bacteria, and although commonly accepted as standard of care in equine medicine, the use of antimicrobials in human snakebite victims is not deemed necessary . Corticosteroids have been used in the treatment of rattlesnake envenomation for decades .…”
Section: Discussionmentioning
confidence: 99%
“…The mouths of rattlesnakes have been shown to harbor a mixed population of bacteria, and although commonly accepted as standard of care in equine medicine, the use of antimicrobials in human snakebite victims is not deemed necessary. 41 Corticosteroids have been used in the treatment of rattlesnake envenomation for decades. 42 An increased mortality in dogs treated with corticosteroids postenvenomation has been reported 43 , but other studies have not shown the same results.…”
Section: Discussionmentioning
confidence: 99%
“…Some envenomations, such as from Cubozoa jellyfi sh, can lead to massive adrenergic surge and cardiovascular collapse. [29][30][31][32][33][34][35][36] …”
Section: Envenomationmentioning
confidence: 99%
“…Among the complex pool of proteins (more than 90% of the dry weight) are included enzymes such as acetylcholinesterases, aminotransferases, phosphoesterases, ADPases, phospholipases, hyaluronidases, L-amino acid oxidases (LAAOs), and proteases (metalloproteinases and serinoproteases) [15]. Protein C activators, growth factors (NGF, VEGF), lectins, precursors of bioactive peptides, von Willebrand factor binding proteins, disintegrins, and bradykinin potentiators are some representatives of nonenzymatic components from snake venom [2, 6].…”
Section: Introductionmentioning
confidence: 99%